2016
DOI: 10.1007/s00126-016-0695-3
|View full text |Cite
|
Sign up to set email alerts
|

Multistage crack seal vein and hydrothermal Ni enrichment in serpentinized ultramafic rocks (Koniambo massif, New Caledonia)

Abstract: International audienceSets of fractures and breccia sealed by Ni-rich silicates and quartz occur within saprock of the New Caledonian regolith developed over ultramafic rocks. The crystallization sequence in fractures is as follows: (1) serpentine stage: lizardite > polygonal serpentine > white lizardite; (2) Ni stage: Ni-Mg kerolite followed by red-brown microcrystalline quartz; and (3) supergene stages. The red-brown microcrystalline quartz corresponds to the very last stage of the Ni sequence and is inferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Importantly, the extensive lateritisation of the peridotite ophiolite resulted in the formation of the worldclass lateritic Ni-Co resources mined in New Caledonia. Genetic models for Ni-Co laterites in New Caledonia involve (i) the leaching of most elements including Mg and Si after hydrolysis of olivine (0.4% Ni) and pyroxene (0.025% Ni), the redistribution and concentration of Ni within the saprolite by substituting Ni for Mg in secondary serpentines with up to 5% Ni and in garnierite veins, which can grade over 20% Ni, and (iii) the development of Ni-bearing oxide-rich (lateritic) horizons at the expense of the saprolite (Butt and Cluzel, 2013;Cathelineau et al, 2016Cathelineau et al, , 2017Freyssinet et al, 2005;Golightly, 2010;Manceau et al, 2000;Trescases, 1975;Wells et al, 2009).…”
Section: Regional Geologymentioning
confidence: 99%
“…Importantly, the extensive lateritisation of the peridotite ophiolite resulted in the formation of the worldclass lateritic Ni-Co resources mined in New Caledonia. Genetic models for Ni-Co laterites in New Caledonia involve (i) the leaching of most elements including Mg and Si after hydrolysis of olivine (0.4% Ni) and pyroxene (0.025% Ni), the redistribution and concentration of Ni within the saprolite by substituting Ni for Mg in secondary serpentines with up to 5% Ni and in garnierite veins, which can grade over 20% Ni, and (iii) the development of Ni-bearing oxide-rich (lateritic) horizons at the expense of the saprolite (Butt and Cluzel, 2013;Cathelineau et al, 2016Cathelineau et al, , 2017Freyssinet et al, 2005;Golightly, 2010;Manceau et al, 2000;Trescases, 1975;Wells et al, 2009).…”
Section: Regional Geologymentioning
confidence: 99%
“…The Raman spectra of polygonal serpentine were first reported by Lemaire (1999) and then Auzende et al (2004) who both identified a unique peak at 3,697 cm −1 with a shoulder at 3,689 cm −1 and a broad secondary peak at 3,646 cm −1 . These publications have since served as a reference for identification of polygonal serpentine on the basis of its Raman spectrum . However, there remains some degree of uncertainty with regard to the Raman signal of polygonal serpentine.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, a recent study of sets of fractures sealed with Ni‐rich silicates and quartz, which generally occur within the fractured bedrock zone of the New Caledonian regolith, revealed a more complex enrichment process through their multiple stage formation. It was inferred that most of the veins represented by Ni‐Mg kerolite accompanied by quartz‐hematite material correspond to the stages of cracking and sealing events that take place in preexisting fractures (Cathelineau, Myagkiy, et al, ). The order of time needed to seal a reopened fracture with pimelite can be estimated in accordance with following expression: {arrayϕ=1ϕinertiNmVm,icm,i,arrayτ=f1(cm,i) where ϕ stands for porosity within the fracture, ϕ inert denotes the volume fraction of nonreactive minerals, set to 0 as we assume sealing only with pimelite, V m is the molar volume of the reactive mineral (L/mol), c m is the mineral concentration that should be expressed in moles of mineral per volume of porous medium (mol/L), and τ is a time of mineral precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, linear extrapolation of the simulation results related to precipitation within the fracture (Figure ) yields its estimated entire clogging over around 150,000 years during the Ni stage (i.e., pimelite formation), assuming the density of pimelite as 2.75 g/cm 3 and, thus, its molar volume ( V m = M / ρ ) as 0.19 L/mol. After, the fracture is meant to be mechanically reopened again which leads to a new stage of mineral precipitations in it, as discussed in Cathelineau, Myagkiy, et al (). It is worth noting that this calculation represents a very first estimate of time needed to seal the fracture since in real systems the permeability of fracture and hence the flux rate through it are expected to reduce progressively with time due to pimelite precipitation.…”
Section: Resultsmentioning
confidence: 99%